Influence of formation methodology on Farmers’ Organizations’ Sustainability - Miyanda, Webster; Shungu, Hamidu; Ngaruko, Deus (IJRDO - Journal of Business Management, 2016)
This study identifies the influence of formation methodologies on the sustainability of Farmers Organisations (FOs) with specific focus on coffee producer groups in Mbeya and Kilimanjaro region and suggests appropriate sustainable formation methods. The research used both purposive and random sampling techniques to enhance the accuracy of sampling. Conducted between February and April 2015 the study was based on FO members and expert informants questionnaire, interviews, FGD and case studies in which both qualitative and quantitative data were collected. The results revealed that well performing FOs were established by PGs as building blocks for secondary organisations. Members described an effective formation method as one, which includes: mobilization, sensitization meetings and a step-by-step process of activities. FO facilitators and producers should adopt a formation process that addresses the needs of PGs and breaks the process into a step-by-step approach to enhance producer understanding. The findings are vital for policies relating to FOs establishment and promotion as well as useful for FO facilitators as they fine-tune their formation interventions to achieve FO sustainability.